Reconstructing Islamic Epistemology: Bridging Metaphysics, Reason, and Revelation - Syafaq, Hammis; Hilmy, Masdar; Musyafaah, Nur Lailatul; Ali, Mohammed Ramadhan Abraheem Alshaykh (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
The modern positivistic paradigm, which places significant emphasis on empirical verification, has led to a shift in the position of Islamic sciences. Islamic sciences, which rely on a balance between revelation, reason, and human experience, have been affected by this shift. In the intellectual history of Islam, the mystical dimension has played an important role in shaping the conception of science. This raises critical questions about the role of Islamic epistemology in contemporary intellectual discourse. This article highlights the need for a reconstruction of Islamic epistemology that unites metaphysics, rationality, and revelation as its main pillars. The prevailing imbalance among these three elements hinders the advancement of Islamic epistemology. By anchoring Islamic epistemology in metaphysics, it aims to present an alternative to the prevailing modern paradigm and contribute to the development of knowledge that is more pertinent to contemporary challenges. The reconstruction of Islamic epistemology seeks to integrate revelation and reason in a more balanced and systematic manner, with metaphysics serving as the conceptual bridge that unites the two. This integration, the study posits, creates new opportunities for dialogue between empirical science and metaphysical understanding, as well as encourages a more holistic perspective in the study of Islam.